On two methods for quantitative unique continuation results for some nonlocal operators - García-Ferrero, María Ángeles; Rüland, Angkana (Communications in partial differential equations, 2020)
In this article, we present two mechanisms for deducing logarithmic quantitative unique continuation bounds for certain classes of integral operators. In our first method, expanding the corresponding integral kernels, we exploit the logarithmic stability of the moment problem. In our second method we rely on the presence of branch-cut singularities for certain Fourier multipliers. As an application we present quantitative Runge approximation results for the operator Ls(D)=∑j=1n(−∂xj2)s+q with s∈[12,1) and q∈L∞ acting on functions on Rn.
Gesehen am 29.06.2021